Evaluation of Feed Resources - International Livestock Research Institute (International Livestock Research Institute, 2014)
Evaluation of existing and potential feed resources in the study sites using Feed Assessment Tool (FEAST) developed by ILRI. The assessment was conducted in three communities in Koutiala cercle (Sirakel?, Zanzoni and Namposs?la) and three communities in Bougouni/Yanfolila cercles (Di?ba, Sibirila and Yorobougoula) in October and November, 2013. In each community, a group discussion involving about 20 key informants was conducted addressing the constraints and opportunities to mixed crop-livestock production systems and livelihood options. In addition to the group discussion, twelve out of the key informants were interviewed for quantitative information on available feed resources ? sources, seasonality, quality, and purchase/sale of feeds. Samples of common feeds mentioned by the interviewees were collected for laboratory analysis. To learn more about this dataset, please visit the ILRI Datasets Portal http://data.ilri.org/portal/dataset/feed_evaluation